Arab Women’s Self-Performance on Instagram - Eiman Khaled Zidan; Noha Mellor (الباحث الإعلامي, 2023)
This study investigates self-perception and self-branding on Instagram among young Arab women in the UAE, focusing on how they curate, negotiate and perform their digital identities and whether their digital self-presentation in any way compromises their sense of authenticity. The study is based on 11 interviews with young women in the UAE, between the ages of 20 and 30, in addition to online observation to follow the participants’ activities on Instagram. The study demonstrates that while social and digital media platforms may play a role in “empowering” Arab women, women tend to set their boundaries of authenticity shaped according to their audience’s expectations and their in-groups. This confirms the role of collectivistic culture in the Arab cultural context, where women may feel more scrutinized than men.